Pengaruh Persepsi Harga, Kualitas Produk, dan Kualitas Pelayanan Terhadap Keputusan Pembelian Furnitur - Depi Ratna Sari; Rama Chandra Jaya; Dadan Abdul Aziz Mubarok (Universitas Persada Indonesia YAI, 2025)
This study aims to examine the effect of price perception, product quality, and service quality on consumers’ purchasing decisions at Koenig Furniture. A quantitative method with descriptive and verificative approaches was employed. The population comprised all Koenig Furniture consumers, with a sample of 100 respondents selected using purposive sampling, a type of non-probability sampling. Data analysis was conducted using Multiple Linear Regression, hypothesis testing (t-test and F-test), and the Coefficient of Determination. The results show that individually, price perception, product quality, and service quality have a positive and significant impact on purchasing decisions, with significance values of 0.000 < 0.05 for each variable. This indicates that appropriate pricing, product durability, and responsive service are crucial factors influencing consumer purchase behavior. Collectively, the three variables also exert a significant simultaneous effect on purchasing decisions, with an F-value of 86.465 and a significance of 0.000. The R² value indicates that 72.1% of the variation in purchasing decisions is explained by price perception, product quality, and service quality, while the remaining 27.9% is attributed to other factors outside the scope of this study.